Tourism and economic growth: comparing Malaysia and Thailand / Noor Adila Idrus - Idrus, Noor Adila (Faculty of Business Management, 2017)
This paper aims at finding out whether tourism give significantly impact on economic growth in both Malaysia and Thailand. Dependent variable used in this study is gross domestic product in both Malaysia and Thailand. On the other hand, the independent variables used in this study are tourist arrival, real exchange rate, consumer price index, and total trade. As for the sample of this study, it comprises of 31 observations on a quarterly basis over eight years period from 2008 to 2015. The methodology used in this study is the Multiple Linear Regression with quarterly time series data has been used to see the relationship between tourism and economic growth. Sources of data for gross domestic product, real exchange rate, and consumer price index in both countries are collected from EIU country data. Data of tourist arrival in Malaysia are collected from Tourism Malaysia Statistic while total trade in Malaysia is collected from Malaysia external Trade Statistic. Data for tourist arrival and total trade in Thailand are collected from Bank of Thailand. A software package called E-views8 will be used in finding and analyzing the data. In order to observe the impact on economic growth in both Malaysia and Thailand an econometric test will be conducted during this research. However, there are few solutions adopted to solve the problems encountered during the research. The results turned out to be convincing and problems are being solved. The final results obtained from every tests in this paper matches with the findings.